Processos de conexão na experiência do Coletivo Movasse - Ester França Monteiro de Barros (2017)
This research provides a reflection on the experience (BONDÍA, 2002) ofColetivo Movasse in the period from 2006 to 2016, especially the connective aspects of collaborative creation in improvisational and performative situations. From a broad perspective, the collective's work, which includes both the organizational culture and artistic practices, uncovers these processes as mediated by artistic creation. This implies the invention of a specific model in which a process is subject to another. Thus, the collective is composed by mature creators-performers who relate to each other in a horizontal, non-hierarchical manner when both creating and dealing with group management. Concerning artisticpractices, specially those in the work Playlist, it is observed that the dancer does not constitute the center of the improvisation, but it represents a relational force (VOLPE, 2011) which is able to develop a collaborative listening. This listening emphasizes and challenges the connection between dancers, besides moving towards a more horizontal and non-hierarchical relationship with the public, the scenic space, the theme, the soundtrack, the scenic objects, lighting and costumes. This strategy aims at providing the audience and the participants with an experience. Inspired by an ethnographic and auto-ethnographic approachto the subject shows that the author of this work is completely involved in the ethics of the Movasse collective, which emphasizes the cultural dimension in this research. Therefore, this Master Thesis focuses on the knowledge derived from experience in dance, which is acquired inside rehearsal rooms and/or performing spaces. The objective is to find ways to direct or convert this knowledge into a contributing element to the performing arts area.